Інноваційна діяльність як складова конкурентного потенціалу підприємства машинобудування - Колотюк, Олена Іванівна (НТУ "ХПІ", 2017)
Сучасні тенденції розвитку світової економіки характеризуються безперервним збільшенням ролі інноваційної діяльності, що приводить до ефективного і стійкого зростання конкурентного потенціалу різних галузей господарської діяльності та машинобудівних підприємств зокрема. Основною задачею для розвитку вітчизняних виробничих підприємств є розвиток і підтримка на всіх рівнях інноваційної діяльності. Стратегічне партнерство на глобальному ринку можливо за допомогою реалізації інновацій, тому найголовнішою особливістю зростання економічних показників стає перехід до процесів і діяльності безпосередньо пов'язаних з інноваціями, що, в кінцевому рахунку, призведе до ефективного зростання конкурентного потенціалу.

Modern trends in the world economy characterized by a continuous increase in the role of innovation activities resulting in efficient and sustainable growth in the competitive capacity of the various sectors of business and engineering companies in particular. The fundamental task for the development of domestic manufacturing companies is to develop and support at all levels of innovation. Strategic partnership in the global market is possible through the implementation of innovation, so the main features of the growth of economic indicators in the transition to becoming processes and activities directly related to the innovations that will ultimately lead to an effective increase in the competitive potential. Innovation activity enables enterprises of mechanical engineering in particular to achieve organizational and technological dominance in the market for goods and services, which in turn contributes to the achievement of a leading position in the competiti on. At the present stage of development of domestic machine-building enterprises is observed rapid focus on the development of innovation in the engineering industry, which in turn requires the improvement of methods of economic calculation.
Innovative activity as a component of the competitive potential of the machine-building enterprise
Keywords: інновації; конкурентоспроможність; економічні відносини; конкурентний потенціал; competitive potential; innovative activity; innovation; competitiveness; mechanical engineering